Identification of Key Candidate Genes for Beak Length Phenotype by Whole-Genome Resequencing in Geese - Huang, Jianhua; Wang, Cong; Ouyang, Jing; Tang, Hongbo; Zheng, Sumei; Xiong, Yanpeng; Gao, Yuren; Wu, Yongfei; Wang, Luping; Yan, Xueming; Chen, Hao (Frontiers in Veterinary Science, 2022)
The domestic goose is an important economic animal in agriculture and its beak, a trait with high heritability, plays an important role in promoting food intake and defending against attacks. In this study, we sequenced 772 420-day-old Xingguo gray geese (XGG) using a low-depth (~1×) whole-genome resequencing strategy. We detected 12,490,912 single nucleotide polymorphisms (SNPs) using the standard GATK and imputed with STITCH. We then performed a genome-wide association study on the beak length trait in XGG. The results indicated that 57 SNPs reached genome-wide significance levels for the beak length trait and were assigned to seven genes, including TAPT1, DHX15, CCDC149, LGI2, SEPSECS, ANAPC4, and Slc34a2. The different genotypes of the most significant SNP (top SNP), which was located upstream of LGI2 and explained 7.24% of the phenotypic variation in beak length, showed significant differences in beak length. Priority-based significance analysis concluded that CCDC149, LGI2, and SEPSECS genes in the most significant quantitative trait locus interval were the most plausible positional and functional candidate genes for beak length development in the XGG population. These findings not only enhance our understanding of the genetic mechanism of the beak length phenotype in geese, but also lay the foundation for further studies to facilitate the genetic selection of traits in geese.